Paradoxical reduction of plasma lipids and atherosclerosis in mice with adenine-induced chronic kidney disease and hypercholesterolemia - Padalkar, Mugdha V.; Tsivitis, Alexandra H.; Gelfman, Ylona; Kasiyanyk, Mariya; Kaungumpillil, Neil; Ma, Danyang; Gao, Michael; Borges, Kelly A.; Dhaliwal, Puneet; Nasruddin, Saud; Saji, Sruthi; Gilani, Hina; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Atherosclerotic cardiovascular disease is prevalent among patients with chronic kidney disease (CKD). In this study, we initially aimed to test whether vascular calcification associated with CKD can worsen atherosclerosis. However, a paradoxical finding emerged from attempting to test this hypothesis in a mouse model of adenine-induced CKD. Methods: We combined adenine-induced CKD and diet-induced atherosclerosis in mice with a mutation in the low-density lipoprotein receptor gene. In the first study, mice were co-treated with 0.2% adenine in a western diet for eight weeks to induce CKD and atherosclerosis simultaneously. In the second study, mice were pre-treated with adenine in a regular diet for eight weeks, followed by a western diet for another eight weeks. Results: Co-treatment with adenine and a western diet resulted in a reduction of plasma triglycerides and cholesterol, liver lipid contents, and atherosclerosis in co-treated mice when compared with the western-only group, despite a fully penetrant CKD phenotype developed in response to adenine. In the two-step model, renal tubulointerstitial damage and polyuria persisted after the discontinuation of adenine in the adenine-pre-treated mice. The mice, however, had similar plasma triglycerides, cholesterol, liver lipid contents, and aortic root atherosclerosis after being fed a western diet, irrespective of adenine pre-treatment. Unexpectedly, adenine pre-treated mice consumed twice the calories from the diet as those not pre-treated without showing an increase in body weight. Conclusion: The adenine-induced CKD model does not recapitulate accelerated atherosclerosis, limiting its use in pre-clinical studies. The results indicate that excessive adenine intake impacts lipid metabolism.